The influence of god class and long method in the occurrence of bugs in two open source software projects: an exploratory study - Cairo, A. S. (2019)
Context: Code smells are associated with poor design and programming style that often degrades code quality and hampers code comprehensibility and maintainability. Goal: In this paper, we investigated to which extent classes affected by the God Class and Long Method code smells were more susceptible to the occurrence of software bugs. Method: We conducted an exploratory study targeting two well known open source software projects, Apache Tomcat and Eclipse JDT Core Component. We applied correlation analysis in order to evaluate to which extent Long Method and God Class were related to the occurrence of bugs. Results: We have found a significant correlation of Long Method and Commits and, on the other hand, a poor correlation of God Class and Commits in the two analyzed projects. Therefore, we expected that the higher the number of occurrences of Long Method, the higher the chances of more commits in a class that contains this method, which could result in the increase of occurrence of bugs. Conclusion: Based on the results, we confirmed what other studies pointed out, regarding classes affected by Long Method being more bug-prone than others. In practice, we found evidence, from analyzed data, that the occurrence of Long Method implies more effort in maintenance tasks.